(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Child sexual assault is a severe violation of human rights and the worst kind of child maltreatment. Child sexual abuse is a threat to public health and not just a private problem, but also has long-term psychological consequences for children in adolescence and adulthood. It was the main aim of this article, not to critically assess each study, rather than perform a systems analysis of the socio demographic profile of victims, and to systematically examine the existing literature. Age data, etc., comprised of secondary sources like journal publications, government documents and media articles, which are part of the socio demographic factors. The scientists investigated children’s sexual assault predicators. Children’s sexual abuse was very prevalent in most major areas included in the research. A frequent misconception amongst criminals is that sex with minors will cure them of HIV (Human immunodeficiency viruses). This article has thus looked at the socio-demographic profile of child sex abuse studies published in the past decade. Initially, the research was confined to women victims of child sexual abuse, but it has been extended to include men who are as susceptible to sexual abuse.